2018
DOI: 10.1007/s10068-018-0527-6
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between fecal bacteria, bile acids and components of tomato pomace

Abstract: The tomato pomace obtained during processing as a residue of tomato processing from large industry. The interactions between tomato pomace and fecal bacteria, bile acids during in vitro digestion were studied. Digestion was carried out by using bioreactor in anaerobic conditions. Tomato pomace can significantly affect the count of fecal bacteria and the solubility of bile acids in in vitro digestion due to bonding ability of their proteins/peptides. The availability and use of bile acids does not only depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…In addition to their differential abundances in individuals with anxiety/ASD compared with healthy controls, there may be a role for these genera in short-chain fatty acid (SCFA)-mediated effects in these disorders. Digestion of tomato pomace in an in vitro model with gut bacteria led to an increase in the concentrations of SCFAs [ 34 ]. Both Blautia and Odoribacter produce SCFAs via fermentation of dietary fiber [ 84 , 86 ], while the abundance of Parabacteroides was correlated with SCFA concentrations in the quail intestinal tract [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their differential abundances in individuals with anxiety/ASD compared with healthy controls, there may be a role for these genera in short-chain fatty acid (SCFA)-mediated effects in these disorders. Digestion of tomato pomace in an in vitro model with gut bacteria led to an increase in the concentrations of SCFAs [ 34 ]. Both Blautia and Odoribacter produce SCFAs via fermentation of dietary fiber [ 84 , 86 ], while the abundance of Parabacteroides was correlated with SCFA concentrations in the quail intestinal tract [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary polyphenols are known to confer many beneficial health effects, including amelioration of inflammation, oxidative stress, and neurodegeneration [ 26 , 27 ]. In particular, citrus fruits [ 28 , 29 ], spinach [ 30 , 31 ], carrots [ 32 ], and tomatoes [ 33 , 34 ] serve as excellent sources of polyphenols and prebiotics. In addition, tomato juice was shown to reduce anxiolytic activity in mice [ 35 ], and tomato consumption confers numerous other beneficial health effects [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the processing of tomatoes, the main residue generated is the tomato pomace [7]. The by-products of tomatoes, especially tomato pomace, are an important source of functional food ingredients such as dietary fiber, β-carotene, lycopene, phenolic acids (ellagic and chlorogenic acids), and flavonoids (rutin and myricetin) [8][9][10][11][12]. They are known as potential factors in decreasing the serum level of oxidative stress biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Akkermansia muciniphila is an intestinal symbiotic bacterium that colonizes the mucosal layer and has a high value in improving host metabolic function and immune response, as well as altering cancer treatment [ 28 ]. Previous studies found that tomato pomace decreased the abundance of Escherichia coli in vitro [ 32 ], and lycopene increased the bacterial alpha diversity and reduced the abundance of Clostridium in mice on a high-fat diet [ 33 ]. Moreover, tomato juice increased mice fecal concentrations of food-derived phenolics, which are essential in modifying the gut microbiota [ 16 ].…”
Section: Discussionmentioning
confidence: 99%